2014
DOI: 10.1111/cmi.12383
|View full text |Cite
|
Sign up to set email alerts
|

Lipid kinases are essential for apicoplast homeostasis inToxoplasma gondii

Abstract: Phosphoinositides regulate numerous cellular processes, by recruiting cytosolic effector proteins and acting as membrane signaling entities. The cellular metabolism and localization of phosphoinositides are tightly regulated by distinct lipid kinases and phosphatases. Here, we identify and characterize a unique phosphatidylinositol 3-Kinase (PI3K) in Toxoplasma gondii, a protozoan parasite belonging to the phylum Apicomplexa. Conditional depletion of this enzyme and subsequently of its product, PI(3)P, drastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 73 publications
2
50
0
Order By: Relevance
“…RT‐PCR confirmed that the TgArk2 catalytic kinase domain transcript (k) was absent in the Tgark2‐ki strain, while the level of TgFYVE1 mRNA used as a loading control was unchanged (Supporting Information Fig. 3C) (Daher et al ., ). The phenotypic consequence of TgArk2 gene disruption was first examined by plaque assay.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…RT‐PCR confirmed that the TgArk2 catalytic kinase domain transcript (k) was absent in the Tgark2‐ki strain, while the level of TgFYVE1 mRNA used as a loading control was unchanged (Supporting Information Fig. 3C) (Daher et al ., ). The phenotypic consequence of TgArk2 gene disruption was first examined by plaque assay.…”
Section: Resultsmentioning
confidence: 97%
“…Plasmids LIC‐CAT‐Ark2Ctg‐3HA and LIC‐CAT‐Ark3Ctg‐3HA were designed to add a sequence coding for a 3HA at the endogenous locus of TGME49_318770 ( TgArk2 ) and TGME49_203010 ( TgArk3 ) open reading frames respectively. A 1101 bp and a 1382 bp fragment corresponding to the 3′ of TgArk2 and TgArk3 respectively were amplified from genomic DNA using primer sets 1/2 and 3/4 respectively and cloned into LIC‐CAT‐3HA vector (Daher et al ., ). Forty micrograms of these plasmids were digested by MluI and ApaI respectively, transfected in the RH‐ku80ko strain and were subjected to chloramphenicol selection.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To further verify his, we expressed dT-fused TgPROP1 and TgPROP2 in lipid kinases-deficient parasite cell lines. They were first expressed transiently in a class III phosphatidylinositol 3-kinase (P13k)- deficient cell line, which is unable to generate both PtdIns3P and PtdIns(3,5)P 2 [34], put in nutrient depleted conditions, and puncta were quantified as described previously (Fig 4B). Depletion of TgPI3k activity severely impaired the formation of TgPROP1- and TgPROP2-positive puncta in these conditions (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, autophagy-related protein 8 and phosphatidylinositol 3-phosphate heavily accumulate on the surface of the apicoplast. However, genetic interference with these mechanisms in T. gondii and Plasmodium falciparum did not produce an unequivocal link to protein import but rather pointed to a broader role of autophagy in apicoplast morphogenesis and inheritance (4648). While the nature of transport across the outermost membrane remains to be revealed, we know more about the PPM that imported proteins encounter next.…”
Section: Discussionmentioning
confidence: 99%